2021
DOI: 10.1038/s41438-021-00693-x
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of flavonoid biosynthesis in Artemisia annua by AaYABBY5

Abstract: Artemisia annua is a medicinal plant rich in terpenes and flavonoids with useful biological activities such as antioxidant, anticancer, and antimalarial activities. The transcriptional regulation of flavonoid biosynthesis in A. annua has not been well-studied. In this study, we identified a YABBY family transcription factor, AaYABBY5, as a positive regulator of anthocyanin and total flavonoid contents in A. annua. AaYABBY5 was selected based on its similar expression pattern to the phenylalanine ammonia lyase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…These cis ‐acting elements have been reported to be recognized by bZIP, bHLH, MYB, WRKY and AP2/ERF TFs to activate the phenylpropanoid pathway in different plants (Han et al., 2021; Hassani et al., 2020; Ji et al., 2021; Zhao et al., 2021; Zhu et al., 2020). For example, AaYABBY5 TF can directly bind to the promoter regions of AaPAL , AaCHI , AaCHS and AaUFGT to positively regulate anthocyanin and flavonoid biosynthesis in Artemisia annua (Kayani et al., 2021). Thus, there are potentially a number of other TFs that regulate these three genes ( MsMYB741 , MsPAL1 and MsCHI ) to synthesize flavonoid, but the ABA‐ABF2‐MYB741‐flavonoid module must be one of the important pathways in regulating flavonoid biosynthesis responsive to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…These cis ‐acting elements have been reported to be recognized by bZIP, bHLH, MYB, WRKY and AP2/ERF TFs to activate the phenylpropanoid pathway in different plants (Han et al., 2021; Hassani et al., 2020; Ji et al., 2021; Zhao et al., 2021; Zhu et al., 2020). For example, AaYABBY5 TF can directly bind to the promoter regions of AaPAL , AaCHI , AaCHS and AaUFGT to positively regulate anthocyanin and flavonoid biosynthesis in Artemisia annua (Kayani et al., 2021). Thus, there are potentially a number of other TFs that regulate these three genes ( MsMYB741 , MsPAL1 and MsCHI ) to synthesize flavonoid, but the ABA‐ABF2‐MYB741‐flavonoid module must be one of the important pathways in regulating flavonoid biosynthesis responsive to abiotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the abundance of TFs (viz., bHLH, NAC, ERF, WRKY, and MYB) indicates their role in mono- and sesquiterpenoid and phenylpropanoid biosynthesis, as reported in previous studies [ 53 , 54 ]. Likewise, the leaf-specific higher enrichments of WRKY, TCP, YABBY, ERF, and MYB suggest their key involvement in regulating terpenoid and flavonoid biosynthesis [ 28 , 55 , 56 , 57 ], while the root-specific enrichment of TFs (viz., Trihelix, WOX, and SBP) probably regulates secondary-metabolite biosynthesis [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the cuticle and trichome, the impact of flavonoid and terpenoid biosynthetic pathways, and trichome development was recently demonstrated in tomato and A. annua (Kang et al, 2014;Shi et al, 2018;Sugimoto et al, 2021). The af mutated tomato, AaYABBY5-overexpressed, and AaTAR2overexpressed A. annua all affect trichome density, flavonoid, and terpenoid biosynthesis (Kayani et al, 2019(Kayani et al, , 2021Zhou et al, 2020;Sugimoto et al, 2021). Our findings demonstrated that terpenoid-related genes and terpenoid metabolites were downregulated in plants with fewer PGTs, compared to controls; however, the variation in flavonoid contents in control plants and plants with fewer PGTs was not significant.…”
Section: Ntmixta Positively Influences Pgt Formation and Monoterpene ...mentioning
confidence: 98%